The Bhagavad Gita a new translation - Flood, Gavin D. 1954-; Martin, Charles 1942- (W. W. Norton & Company, 2012)
A new translation of the classic Hindu text about virtue featuring a dialogue between Krishna and the warrior Arjuna before a battle over succession to the throne.